Theory of type-II superconductivity in ferromagnetic metals with triplet pairing - Mineev, V.P. (Физика низких температур, 2018)
The superconducting state in uranium compounds UGe₂, URhGe and UCoGe is formed at temperatures far below the Curie temperature pointing on nonconventional nature of superconductivity in these materials — namely the superconductivity with triplet pairing. The emergence of superconductivity is accompanied by the slight magnetization expulsion typical for the type-II superconductors. Following classic Abrikosov paper I develop the theory of type-II superconductivity in application to two-band ferromagnetic metal with equal spin triplet pairing.